Guidelines for BIM implementation in the environmental assessment of social housing - Alvarez, Analía Alejandra; Ripoll, Verónica; Campos, Laura; Ortega, Andrés (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
Innovations in science and technology play a key role in the transition to cleaner production. Based on this, this article seeks to promote the practical integration of concepts of bioclimatic architecture in the design of social housing, in real-time and from its initial stages through the development of a working mechanism applicable to the design stage as a decision support system during the planning process. The methodology consists of modeling with BIM (Building Information Modeling) and with ENERGYPLUS three prototypes of social housing in generalized use in the city of San Juan, Argentina. From the comparative analysis of the results achieved, the similarities and divergences associated with the use of the selected software for the environmental evaluation of social housing emerge, thus setting the basic guidelines for carrying out the BEM (Building Energy Modeling) of the same.